FEATURES INVOLVED IN MARKETING THE “PEN” DIGITALLY - Prasanth, V Sai; Kathik, Mogalapalle V; Vardhan, P Vishnu; Kumar, Ravupalli Prasanna; Venkataswamy, Galla (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the digital marketing strategies and features involved in effectively promoting the “PEN” to online consumers. Key features include targeted social media advertising, search engine optimization (SEO), and influencer partnerships, all of which contribute to increasing visibility and engagement for this simple yet essential product. Personalization techniques allow brands to tailor messaging to specific audiences, while e-commerce integration facilitates a seamless path from discovery to purchase. Additionally, user-generated content and reviews build trust and authenticity, enhancing the pen's appeal. By leveraging data analytics, brands can monitor trends, optimize campaigns, and measure customer response in real-time, ultimately refining strategies to boost conversions and brand loyalty in a competitive digital market.